2015
DOI: 10.1016/j.ymgme.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal storage disease: Gene therapy on both sides of the blood–brain barrier

Abstract: Most lysosomal storage disorders affect the nervous system as well as other tissues and organs of the body. Previously, the complexities of these diseases, particularly in treating neurologic abnormalities, were too great to surmount. However, based on recent developments there are realistic expectations that effective therapies are coming soon. Gene therapy offers the possibility of affordable, comprehensive treatment associated with these diseases currently not provided by standards of care. With a focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 151 publications
0
20
0
Order By: Relevance
“…It is remotely possible that the enzyme replacement therapy (ERT) taken by our GD patients may affect progression of PD as all of the patients in our cohort were receiving long-term ERT. However, this ERT, a macrophage-targeted large glycoprotein (MW ≈ 68 kDa) is considered not to cross the blood–brain barrier [32]. Alternatively, ERT may have systemic effects; which in turn indirectly affects the central pathology of PD.…”
Section: Discussionmentioning
confidence: 99%
“…It is remotely possible that the enzyme replacement therapy (ERT) taken by our GD patients may affect progression of PD as all of the patients in our cohort were receiving long-term ERT. However, this ERT, a macrophage-targeted large glycoprotein (MW ≈ 68 kDa) is considered not to cross the blood–brain barrier [32]. Alternatively, ERT may have systemic effects; which in turn indirectly affects the central pathology of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In the MPS models several reactions associated with ROS production increased their flux values, such as cytochrome C oxidase, NADH dehydrogenase, and the activation of protective mechanism as glutathione. Although several studies have shown the processes affected in some MPS animal models I Glycine reversible transport via proton symport (lysosome) I Iduronate transport (lysosome) D L-alanine reversible transport via proton symport (lysosome) I L-proline reversible transport via proton symport (lysosome) I N-acetylneuraminate transport (lysosome) D Transport of L-Histidine by hPT3 or hPT4 peptide transporters I UDP intracellular transport I UDP-N-acetyl-galactosamine intracellular transport D and cells [62][63][64][65], the present study shows for the first time, for all MPS an analysis of the adaptation to the metabolism alterations caused by the blocking of GAG catabolism. Understanding this adaptation process may contribute to understand the pathophysiology of these diseases and to identify therapeutic targets and biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal storage diseases (LSDs) consist of 50 rare inherited disorders that are because of specific defects in lysosomal function. Specifically, LSDs result from the lack of a single enzyme essential for the metabolism of lipids, glycoproteins (sugar‐containing proteins), or mucopolysaccharides (Aronovich and Hackett ; Parenti et al . ).…”
Section: Mitochondria and Lysosomal Storage Disordersmentioning
confidence: 99%